Race and Slavery in the Middle East: An Historical Inquiry By Bernard Lewis. New York: Oxford University Press. 1990, 169 pp. (American Journal of Islam and Society, 1993)
This book is based mainly on an earlier small book entitled Race andColor in Islam that was published in 1971. In this new edition, Lewisadded more chapters and expanded the discussion of some of the materialthat he examined in the earlier edition. He mentions that scholarly workon the topic of slavery received only limited attention from researcherscompared with studies on slavery in the Greek and Roman worlds. Onlya few number of studies of high caliber could be cited.The main theme of the book, as Lewis states clearly in his concludingremarks, is that Islam's total racial hannony and ilUlocence is a mythcreated, maintained, and idealized by westerners as a rebuke to the actionsof the white man in the Americas and South Africa. Moreover, theidea found relevance among missionaries in Africa who tried to seek explanationsfor their failure in contrast to the success of Islam.In his analysis, Lewis tries lo distinguish between three distinct meaningsof Islam: 1) Islam as the religion taught by the Prophet and prescribedin the Qur'an; 2) Islam as a larger body including the traditions,works, and fatwas of Islamic scholars and jurists. In this regard Islam includesthe Shari'ah as developed over the centuries; and 3) Islam as thecounterpart not of Christianity but of Christendom. Here, Islam means not ...